Delayed Appearance of Cutaneous Lesions of Cutaneovisceral Angiomatosis (CAT) Leading to Misdiagnosis of Immune Thrombocytopenia. Issue 4 (May 2017) - Com, Gulnur; Awad, Samah; Trenor, Cameron C.
Abstract : Cutaneovisceral angiomatosis with thrombocytopenia (CAT), also called multifocal lymphangioendotheliomatosis with thrombocytopenia (MLT), is a rare and newly described vascular malformation. Skin manifestations and thrombocytopenia are the hallmark of CAT/MLT, and visceral lesions are described. We report an infant with pulmonary hemorrhage, thrombocytopenia, and antiplatelet antibodies. There was no cutaneous involvement and the child was initially diagnosed with immune thrombocytopenia. Poor response to immune thrombocytopenia–directed therapy raised suspicion for an alternative diagnosis, and the ultimate diagnosis of CAT/MLT was made by lung tissue sampling. Unexpectedly, 2 years after resolution of pulmonary lesions and thrombocytopenia, the child developed typical cutaneous lesions. Abstract : Supplemental Digital Content is available in the text.